![](https://rs.olm.vn/images/avt/0.png?1311)
Hãy nhập câu hỏi của bạn vào đây, nếu là tài khoản VIP, bạn sẽ được ưu tiên trả lời.
![](https://rs.olm.vn/images/avt/0.png?1311)
![](https://rs.olm.vn/images/avt/0.png?1311)
13/50+9/100+41/100+12/50
=(13/50+12/50)+(9/100+41/100)
=1/2+1/2
=1
11) Ta có:
\(\frac{120-0,5.40.5.0,2.20.0,25-20}{1+5+9+...+33+37}\)
\(=\frac{120-\left(0,5.40\right).\left(5.0,2\right).\left(20.0,25\right)-20}{1+5+9+...+33+37}\)
\(=\frac{120-20.1.5-20}{1+5+9+...+33+37}\)
\(=\frac{120-100-20}{1+5+9+...+33+37}\)
\(=\frac{0}{1+5+9+...+33+37}=0\)
![](https://rs.olm.vn/images/avt/0.png?1311)
\(a.\dfrac{3}{5}-\dfrac{-7}{10}-\dfrac{13}{-20}=\dfrac{12}{20}-\dfrac{-14}{20}-\dfrac{-13}{20}=\dfrac{12-\left(-14\right)-\left(-13\right)}{20}=\dfrac{39}{20}\)
\(b.\dfrac{3}{4}+\dfrac{-1}{3}-\dfrac{5}{18}=\dfrac{3}{4}+\left(\dfrac{-6}{18}-\dfrac{5}{18}\right)=\dfrac{3}{4}+\dfrac{-11}{18}=\dfrac{27}{36}-\dfrac{-22}{36}=\dfrac{49}{36}\)
\(c.\dfrac{3}{13}-\dfrac{5}{-8}+\dfrac{-1}{2}=\dfrac{3}{13}-\left(\dfrac{5}{-8}+\dfrac{-4}{8}\right)=\dfrac{3}{13}-\dfrac{1}{8}=\dfrac{24}{104}-\dfrac{13}{104}=\dfrac{11}{104}\)
\(d.\dfrac{1}{2}+\dfrac{1}{-3}=\dfrac{3}{6}+\dfrac{-2}{6}=\dfrac{1}{6}\)
\(a,\dfrac{3}{5}-\dfrac{-7}{10}-\dfrac{13}{-20}\)
\(=\dfrac{12}{20}+\dfrac{14}{20}+\dfrac{13}{20}\)
\(=\dfrac{12+14+13}{20}\)
\(=\dfrac{39}{20}\)
\(b,\dfrac{3}{4}+\dfrac{-1}{3}-\dfrac{5}{18}\)
\(=\dfrac{27}{36}+\dfrac{-12}{36}-\dfrac{10}{36}\)
\(=\dfrac{27+\left(-12\right)-10}{36}\)
\(=\dfrac{5}{36}\)
\(c,\dfrac{3}{13}-\dfrac{5}{-8}+\dfrac{-1}{2}\)
\(=\dfrac{24}{104}-\dfrac{-65}{104}+\dfrac{-52}{104}\)
\(=\dfrac{24-\left(-65\right)+\left(-52\right)}{104}\)
\(=\dfrac{37}{104}\)
\(d,\dfrac{1}{2}+\dfrac{1}{-3}\)
\(=\dfrac{3}{6}+\dfrac{-2}{6}\)
\(=\dfrac{3+\left(-2\right)}{6}\)
\(=\dfrac{1}{6}\)
![](https://rs.olm.vn/images/avt/0.png?1311)
Bài 1:
\(A=\frac{3333}{101}\left(\frac{1}{12}+\frac{1}{20}+\frac{1}{30}+\frac{1}{42}\right)=\frac{3333}{101}\left(\frac{1}{3.4}+\frac{1}{4.5}+\frac{1}{5.6}+\frac{1}{6.7}\right)\)
\(A=\frac{3333}{101}\left(\frac{1}{3}-\frac{1}{4}+\frac{1}{4}-\frac{1}{5}+\frac{1}{5}-\frac{1}{6}+\frac{1}{6}-\frac{1}{7}\right)\)
\(A=\frac{3333}{101}\left(\frac{1}{3}-\frac{1}{7}\right)=\frac{3333}{101}.\frac{4}{21}=\frac{1111.4}{101.7}=\frac{4444}{707}\)
Bài 2
\(A=\frac{2^{10}+1}{2^{10}-1}=\frac{2^{10}-1+2}{2^{10}-1}=1+\frac{2}{2^{10}-1}\)
\(B=\frac{2^{10}-1}{2^{10}-3}=\frac{2^{10}-3+4}{2^{10}-3}=1+\frac{4}{2^{10}-3}\)
Ta thấy \(2^{10}-1>2^{10}-3\Rightarrow\frac{2}{2^{10}-1}< \frac{2}{2^{10}-3}< \frac{4}{2^{10}-3}\)
Từ đó \(\Rightarrow1+\frac{2}{2^{10}-1}< 1+\frac{4}{2^{10}-3}\Rightarrow A< B\)
Bài 3\(P=\frac{\left(\frac{2}{3}-\frac{1}{4}\right)+\frac{5}{11}}{\frac{5}{12}+\left(1-\frac{7}{11}\right)}=\frac{\frac{5}{12}+\frac{5}{11}}{\frac{5}{12}+\frac{4}{11}}=\frac{\frac{55+60}{11.12}}{\frac{55+48}{12.11}}=\frac{115}{103}\)
![](https://rs.olm.vn/images/avt/0.png?1311)
\(\frac{7}{13}.\frac{5}{19}+\frac{7}{19}.\frac{8}{13}-\frac{37}{19}=\frac{1}{19}\left(\frac{5.7}{13}+\frac{7.8}{13}-37\right)=\frac{1}{19}\left(\frac{91}{13}-37\right)=\frac{1}{19}.\left(-30\right)=-\frac{30}{19}\)